In-duct beamforming and mode detection using a circular microphone array for the characterisation of broadband aeroengine fan noise. - Caldas, Luciano Coutinho (2016)
The development of technologies to reduce turbofan engine noise reveals the fan noise, the first stage of an engine, as a great contributor for the total noise of an airplane. So a better understanding of the fan noise generation came up and motivated the construction of a fan rig test facility at the University of São Paulo in São Carlos by a partnership between the university and EMBRAER S.A.. The fan rig is composed of a long duct (12mlong) comprising a 16-bladed fan rotor and 14-vaned stator. The rotor is powered by an 100 hp electrical motor allowing speed up to 4250 RPM resulting in 0.1Mach axial flow. A 77-microphone wall-mounted array was designed for fan noise analysis. A cooperation with NASA-Glenn allowed data and information exchanging from their similar fan rig setup, the ANCF, grating then the validation of the in-house developed software. A short guide for duct-array is proposed in this work. Complex software was developed to process the data from the microphones array. We performed 3 different types of analysis: power spectral density, noise imaging obtained by acoustic beamforming and modal analysis.We proposed a different technique for modal analysis based on beamforming images in this work.We did not find any similar technique in the references. The results obtained by this technique were validated with data from ANCF-NASA. Comparative results are presented for both fan rigs, such as: power spectral densities for different fan speeds, modal analysis at the blade passing frequency (strong tones generated by the fan), noise imaging obtained by beamforming for rotating and static noise sources. Finally, results achieved in this work are in agreement with those observed in the references consulted.